Potential risk assessment of metals in edible fish species for human consumption from the Eastern Aegean Sea. Issue 1 (15th July 2017) - Pazi, Idil; Gonul, L. Tolga; Kucuksezgin, Filiz; Avaz, Gulsen; Tolun, Leyla; Unluoglu, Aydın; Karaaslan, Yakup; Gucver, S. Mine; Koc Orhon, Aybala; Siltu, Esra; Olmez, Gulnur
Abstract: The levels of Hg, Cd, Pb, Cr, Cu and Zn were measured in the tissues of four edible fish species namely: Diplodus annularis, Pagellus erythrinus, Merluccius merluccius and Mullus barbatus, collected from the Turkish Coast of the Aegean Sea. Except for D. annularis, the levels of Cd and Pb in all fish tissues sampled in Aliaga Bay in 2009 were above the tolerable limits according to the Food and Agriculture Organization of the United Nations (FAO). Hg in P. erythrinus and M. barbatus were higher than the maximum permitted limits (FAO), while D. annularis and M. merluccius were lower than the limit for biota in the district of Aliaga. Although the Target Hazard Quotient (THQ) values for Cd, Pb, Cu, Cr, Zn in all fish samples were lower than 1.0, the THQ for Hg levels were higher than 1.0 for most of the samples. According to the THQ values, M. merluccius may be consumed in moderation from Aliaga Bay, while the consumption of M. barbatus and P. erythrinus collected from Aliaga Bay are potentially hazardous to human health due to the Hg concentrations. Fish collected from Izmir Bay can be consumed safely. Highlights: Hg, Cd, Pb, Cr, Cu, Zn were measured in fish species from Izmir and Aliaga Bays. Hg in some fish species were higher than the maximum permitted limits of FAO. Fish collected from Izmir Bay can be consumed safely. The consumption of some fish from Aliaga Bay can cause several health risks.